2019
DOI: 10.13111/2066-8201.2019.11.3.10
|View full text |Cite
|
Sign up to set email alerts
|

GNSS Navigation Threats Management on-Board of Aircraft

Abstract: This paper proposes low-complexity measures to be deployed on most aircraft to enable the management of Global Navigation Satellite Systems (GNSS) interference, and in particularly of jamming and spoofing threats, in order to reach the Flightpath2050 safety and security targets. It is known that, if there is a jamming interference and GNSS navigation is lost, a disruption will be caused, requiring the likely intervention of Air Traffic Control. Also, the presence of a spoofing signal is a serious security thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It shows the jamming detection results for test scenario OF-JAM.Z2D-Test 11, described in Section 5 using all the detectors described in Section 3 . All the considered detectors with the current recorded tests show that they work perfectly well under realistic scenarios and they confirm the previous findings of the authors based on simulations and lab-tests as reported in [ 1 , 19 , 37 ]. In particular, the estimated Probability of Detection ( ) is 100%, and the Probability of False Alarm ( ) is 0.…”
Section: On-field Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…It shows the jamming detection results for test scenario OF-JAM.Z2D-Test 11, described in Section 5 using all the detectors described in Section 3 . All the considered detectors with the current recorded tests show that they work perfectly well under realistic scenarios and they confirm the previous findings of the authors based on simulations and lab-tests as reported in [ 1 , 19 , 37 ]. In particular, the estimated Probability of Detection ( ) is 100%, and the Probability of False Alarm ( ) is 0.…”
Section: On-field Resultssupporting
confidence: 90%
“…The mentioned methods have been applied both in the lab on synthetic signals, as presented in [ 19 ], and on live signals recorded during the open-field test campaign described hereafter. The results of the latter test campaign are reported in Section 6.1 of this paper.…”
Section: Methods For Jamming Detection and Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Commonly used processing methods in the time domain include enhanced correlator techniques represented by the narrow correlator technique [ 16 , 17 ] and parameter estimation methods represented by the MEDLL technique (Multipath Estimate Delay Lock Loop) [ 18 , 19 ]. The process of spatial signal processing is mainly based on the fact that the LOS (line of sight) signal and multipath noise reach the receiver from different spatial directions; therefore, multipath interference suppression can be achieved using adaptive signal processing with multiple antennas [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%